SCROTAL PYOCELE ASSOCIATED WITH SODIUM-GLUCOSE CO-TRANSPORTER 2 INHIBITOR (SGLT2i): THE NEED FOR HIGH INDEX OF SUSPICION - Thewjitcharoen, Yotsapon; Lekpittaya, Nampetch; Nakasatien, Soontaree; Polchart, Somsong; Chaimuangraj, Suchart; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Recent data showed that SGLT2i is linked with Fournier gangrene. Scrotal pyocele is a rare clinical condition often commonly associated with acute epididymoorchitis. Previous evidence suggested potential risk of serious genitourinary infection in patients using SGLT2i. however, scrotal pyocele associated with SGLT2i has never been reported. CASE A patient with poorly-controlled type 2 DM on SGLT2i presented with acute scrotal pain. CONCLUSION Although rare, SGLT2i may result in serious genitourinary infection including scrotal pyocele. Clinicians must take great care when prescribing SGLT2i to elderly male patients with pre-existing hydrocele. Treatment requires broadspectrum antibiotics and emergent surgical consultation to prevent testicular damage or Fournier gangrene.